Immunological imprint on peripheral blood in kidney transplant recipients after two doses of SARS-CoV-2 mRNA vaccination in Japan - Takiguchi, Shinya; Tomita, Yusuke; Uehara, Saeko; Tateishi, Koichiro; Yamamoto, Norio; Nakamura, Michio (Frontiers in Medicine, 2022)
The immunological imprint after two doses of severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2) mRNA vaccination for patients after kidney transplantation (KTx) remain unclear. This study included KTx recipients and volunteer healthy controls (HCs) who received two doses of SARS-CoV-2 mRNA vaccine (Pfizer BioNTech) from January 2021 to December 2021. We analyzed safety within 21 days after each vaccination dose and compared the immune response in peripheral blood mononuclear cells (PBMCs) between the two groups. No graft rejection was observed throughout this study. Adverse events were generally observed within 5 days. The KTx group exhibited a significantly lower degree of symptoms between doses 1 and 2 (P<.001). Increases in activated subsets of T and B cells expressing human leukocyte antigen (HLA)-DR and/or CD38 were observed in the HC group after dose 2 (both P<.001), with the greatest increases in HLA-DR+CD8+ T cells and CD38+CD19+ B cells (P=.042 and P=.031, respectively). In addition, PD1+CD8+ T cells—but not PD1+CD4+ T cells—increased significantly in the HC group (P=.027). In the KTx group, however, activated HLA-DR+, CD38+, and PD1+ cells remained at baseline levels. Immunoglobulin (Ig)G against SARS-CoV-2 was detected in only four KTx recipients (13.3%) after dose 2 (P<.001). Multivariate logistic regression analyses revealed that ∆HLA-DR+CD8+ T cells and ΔCD38+CD19+ B cells were significantly associated with IgG formation (both P=.02). SARS-CoV-2 mRNA vaccine generates impaired cellular and humoral immunity for KTx recipients. Results indicate the need for modified vaccination strategies in immunocompromised KTx recipients.